Social Participation of Students With a Migration Background—A Comparative Analysis of the Beginning and End of a School Year in German Primary Schools - Hamel, Niklas (Frontiers in Education, 2022)
The social participation of students can be defined as one of the fundamental goals of inclusion. However, current literature shows that (a) children from minorities can belong to groups at risk of low social participation and (b) relatively little is known as yet about changes in social participation over time (longitudinal study). This study therefore seeks to investigate more closely the stability of social participation for students with a migration background. A total of 353 year 4 students (158 45% girls, including 58 16% with German as their second language) from North Rhine-Westphalia (Germany) were surveyed about their social participation (friendships, interactions, etc.) using a paper-and-pencil questionnaire at the beginning (September 2018) and at the end (June/July 2019) of a school year. All schools of common learning in North Rhine-Westphalia were contacted and asked to participate voluntarily. Only students who participated in the survey at both measurement points were considered. At the first measurement point, students had an average age of 9 years (SD = .42; range 8-11). At the second measurement point, students had an average age of 10 years (SD = .57; range 9-12). Student responses were largely in the form of sociometric ratings or sociometric nominations. One finding of the variance analyses (ANOVA with repeated measures) was that, for the most part, there was no difference longitudinally between students with and those without a migration background. However, students with a migration background were found to have significantly fewer stable friendships than their peers. No other differences in relation to changes over time were recorded in any other areas. The findings thus also illustrate that a possible lack of social participation by students with a migration background remains constant, and that the period when students first come into contact with each other appears to be of fundamental importance.